(#)Stayhome hashtag As A Social Campaign To Prevent The Covid 19 through Instagram in Makassar City - Nugrah Juniar Umar (State Islamic Institute of Bone, Indonesia, 2020)
AbstractPeople these days know as an actif and had creativity to receive and share the message. As what happened today that world is busy to face the covid 19. To stop the virus, Najwa Shihab spread the #stayhome hashtag as a social movement to study, work and pray at home which is an instruction by the government. This #stayhome hashtag published by social media in Instagram to persuade and to educate people to stay at home. The purpose of this research is to explain the effectiveness of #stayhome hashtag as a social campaign to prevent covid 19. The methods of the research are qualitative that will explain the phenomenon about #stayhome hashtag by using AIDA model (Attention, Interest, Desire an Action). The result shows that by using #stayhome hashtag effectively use as a social campaign to prevent covid 19. This result proves that there is an attention, interest, desire and action that mentioned by informants. This also found that people use the hashtag had any motivates, those are to be exist, to share creativity about activities at home, to persuade people to participate and as an effort to prevent the covid 19. The changes in behavioral of people who used the hashtag also visible in Instagram with the number of 5,355,665 photos uploaded and still counting. Keywords: Covid 19; Hashtag; #stayhome; Social Campaign.